2019
DOI: 10.18502/jhs.v7i2.1063
|View full text |Cite
|
Sign up to set email alerts
|

Air born bacteria evaluation in the kitchen air of restaurants in Babol City

Abstract: Background and purpose: Bioaerosols enter into human body through various ways (inhalation, ingestion or skin absorption). The aim of this study was to investigate the type and density of the predominant bacteria in two seasons - cold and warm - in the kitchen air of restaurants. Materials and Methods: This descriptive cross-sectional study was conducted on the air of restaurants' kitchen in Babol. Sampling was performed by using a personal sampling pump with impinger tank using a flow rate of 4 l/min du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This may be linked to the fact that sunlight has disinfection properties and has the ability to destroy some bacteria. These observations have been supported by earlier reports that proper design of ventilated restaurants and its location could enable sun rays to prevent bioaerosol air pollution (Asgharzadeh et al, 2019). In contrast to the present findings, Mushtaq et al (2011) (Chikere et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be linked to the fact that sunlight has disinfection properties and has the ability to destroy some bacteria. These observations have been supported by earlier reports that proper design of ventilated restaurants and its location could enable sun rays to prevent bioaerosol air pollution (Asgharzadeh et al, 2019). In contrast to the present findings, Mushtaq et al (2011) (Chikere et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…from restaurants in Nigeria. Also, the results of the present study were also found to be similar with that of Asgharzadeh et al (2019) The presence of cocci in the air of the restaurants was not only due to overcrowding but also poor ventilation (Awad, 2007), and Gram-positive bacilli presence can be attributed to a number of outdoor sources, such as soil emissions, water, dust, air, vegetation, wounds and abscesses (Aydogdu et al, 2010). The average densities of bacteria in the restaurants were lower than WHO recommendation and guidance ACGIH (guideline value of 500 CFU/m 3 ).…”
Section: Discussionsupporting
confidence: 80%